Visibilidade do projeto de extensão cesta básica no município de Tupã - Bruvers, Jéssica [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Machado, João Guilherme Camargo Ferraz [UNESP]; Nogueira, Erica dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to report and evaluate the experience from the university extension activity called "Basic Food Basket", which takes place in the city of Tupa / SP since 2006. The study sought through interviews with reporters from radio, newspaper and television channels, in which the results are disseminated, get the visibility of information about the project. There is a big interest from local channels of communication on the information generated by the project, suggesting its real importance for the beneficiaries of the project - the population of the region.

O presente trabalho tem como objetivo relatar e avaliar a experiência resultante da atividade de extensão universitária denominada “Cesta Básica”, que ocorre no município de Tupã/SP, desde 2006. O trabalho buscou, por meio de entrevistas com os repórteres de rádios, jornais e canais de televisão, no qual são divulgados os resultados, obter a informação da visibilidade acerca do projeto. Verifica-se um grande interesse por parte dos canais de comunicação locais nas informações geradas pelo projeto , sugerindo sua real importância para os beneficiários do projeto – a população da região.
Keywords: Basic food basket; Cost; Visibility; Cesta básica; Custo; Visibilidade